2013
DOI: 10.7567/jjap.52.11nj05
|View full text |Cite
|
Sign up to set email alerts
|

Property Variation of Ni–W Electroformed Mold for Micro-Press Molding

Abstract: We proposed a simple method to fabricate a Ni–W electroformed mold for glass micro-press molding. For example, borosilicate glass (D263) was molded using the Ni–W electroformed mold. A Ni–W electroformed mold with a fine line was fabricated by photolithography and electroforming technology. Additionally, the Ni–W electroformed mold did not require a release layer. As the result of molding D263 at 883 K, the minimum pitch of the glass pattern was the same as that of the Ni–W electroformed mold. We argue that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The current density and temperature of the Ni-W bath were 1200 A=m 2 and 60 °C, respectively, with reference to the Ni-W mold for borosilicate glass. 22) The plating time was 5 min. We observed the surfaces of each obtained Ni-W film by field emission scanning electron microscopy (FE-SEM; FEI XL-30Sirion).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current density and temperature of the Ni-W bath were 1200 A=m 2 and 60 °C, respectively, with reference to the Ni-W mold for borosilicate glass. 22) The plating time was 5 min. We observed the surfaces of each obtained Ni-W film by field emission scanning electron microscopy (FE-SEM; FEI XL-30Sirion).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…21) Additionally, we showed the usability of Ni-W plating film as mold material of glass imprinting to satisfy the chemical stability, and heat resistance requirements. 22) However, an anomalous microspike called a nodule is easily formed on the Ni-W surface. Numerous studies have been reported concerning the nodule.…”
Section: Introductionmentioning
confidence: 99%
“…In mold fabrication, a low thermal-expansion alloy is commonly used as a dummy substrate for the deposition of Ni–W during electroforming. For example, Yasui et al [ 60 ] reported a simple approach for Ni–W alloy mold fabrication using conventional lithography and electroforming. They used Incoloy909, a low coefficient of thermal expansion (CTE: 7.7 µm/m/°C) as a mold substrate.…”
Section: Mold Materials For Precision Glass Moldingmentioning
confidence: 99%
“…Some examples of glass molding experiments that have employed Ni and Ni alloy molds are summarized in Table S2 in the Supplementary Material of S2 [ 50 , 55 , 56 , 57 , 58 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Ni and Ni alloy molds have high mechanical hardness, high corrosion resistance, and lower thermal expansion coefficients.…”
Section: Mold Materials For Precision Glass Moldingmentioning
confidence: 99%
“…4) We used SU-8 as the master mold for a Ni-W electroformed mold. 5) However, SU-8 microstructures are unsuitable for many applications requiring nanostructures, such as an optical fiber localized surface plasmon resonance (LSPR) biosensor, 6) and a subwavelength structure for solar cell application. 7) Ultraviolet (UV) exposure is not used for processing nanostructures because of the limit of the UV wavelength (350-400 nm).…”
mentioning
confidence: 99%